Evaluasi Strategi Cara Memasarkan Produk Umkm Dengan Menggunakan Sistem Informasi Di Era Digital - Dian Farindah Damanik; Muhammad Irwan Padli Nasution (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
. In today's rapidly developing digital era, product marketing strategies for Micro, Small and Medium Enterprises (MSMEs) are becoming increasingly important to compete and develop. Information Systems (SI) have become a very effective tool in helping MSMEs optimize the marketing of their products. This research aims to evaluate strategies for marketing MSME products using IS in the digital era. The research method used is descriptive research with a qualitative approach. Data was collected using the literature method. The results of this research show that the use of IS in marketing MSME products has several significant benefits, such as increasing online visibility, enabling personalization in product offerings, and facilitating interaction with customers via digital platforms. This research provides a more in-depth view of how MSMEs can utilize IS to market their products in the digital era. The practical implication is that MSMEs need to invest time and resources in understanding and implementing IS in their marketing strategies, while also paying attention to the challenges that may arise. In this way, MSMEs can maximize their potential in marketing their products effectively and competing in an increasingly competitive digital market.